Evaluasi Faktor Keberhasilan dan Kepuasan Pengguna Sistem Informasi Pengaduan Online Kota Malang - Kanthi, Yekti Asmoro; Aminah, Siti (Jurnal Teknologi dan Manajemen Informatika, 2023)
An online complaint application has been launched to bridge the aspirations, complaints, and grievances of the community to the municipal government of Malang. This application is used to facilitate the public in submitting their complaints with the hope of receiving prompt responses and immediate follow-up actions. Although the online complaint application can be accessed by users, in reality, the administrators responding to public complaints still undergo a very lengthy process, and some complaints are left unanswered. There are many obstacles, both within and outside the system, suspected to be the causes of the slow response by administrators to public complaints. For example, the lack of a super administrator, budget constraints, frequent personnel turnover in the Diskominfo apparatus, some regional devices lacking synchronization, and challenges related to commitment guidance and inadequate socialization. This is due to many operational and managerial aspects that may not have been running as they should. Therefore, an evaluation of the success factors of the use of the online complaint system needs to be conducted using the HOT-Fit Model (Human Organization Technology—Net Benefits). The aim of this research is to identify the factors that hinder the effectiveness of the online complaint system.